Andalusian Woman Customs Traditions Challenge and Change - Areeg Kareem Hamd Hatif (College of Education for Women, 2019)
A study Andalusia woman in shade society Arabic Islamic conservative on social customs in respect instructions in the different cover and tongue and not reveal beautiful woman because she is development the honor conscience in the society and she is respect not mix with the men about fall what he said the law Islamic and belief that the Andalusian people prince Husham days ago and he entry dependence to the mawta book. But the Andalusia woman was having the freedom and boasting and the greatness and beautiful and not respected factions from Andalusia woman instruction religion fewness commitment in the tradition Arabian and Islamic her promiscuity her promiscuity in the Spanish society that it is different habits and traditions with society Islamic and existence habits the event and parties and phenomenon adorn using cosmetics at Andalusian woman that the almoner and habits appear and caplets conducts like the accord said (( how young on thing young man on him)) about that outbreak in Andalusia since reign emirate and challenge honor Islamic as well as with phenomenon maids through the campaigns and forays outbreak markets blacksmiths and the Andalusian society become in conflict with habits and recommendations Islamic and the society breakup between denomination respect the habits and traditions and second denomination remain live fun and affluence and mocking in aesthetics Andalusian woman.